Congenital Hypothyroid: Report of Two Cases With Emphasis On Clinical Diagnosis And Brief Review of Relevant Literature - Inda D. Arif; A. S. Ongkie (Paediatrica Indonesiana, 1984)
Two cases of congenital hypothyroidism diagnosed clinically have been presented. Clinical improvement during substitution therapy with Thyranon was evident. The importance of clinical diagnosis has been emphasized. Awareness of the condition has been stressed as being of urgent necessity to diagnose accurately. Relevantt literature was briefly reviewed.